Effects arbuscular mycorrhizal fungi interactions and sewage sludge application on heavy metal phytoremediation in mine tailings - Sayın, Fatma Ece. (Thesis (M.S.)-Bogazici University. Institute of Environmental Sciences, 2019., 2019)
Phytoremediation can be enhanced by the substantial symbiotic relationship between Arbuscular Mycorrhizal Fungi (AMF) and the hyperaccumulator plants (sunflower). AMF set up intimate hyphal network of fungi with the host plant root and enables nutrient, water and heavy metal uptakes. Additionally, application of sewage (wastewater) sludge as a soil amending material improves the phytoremediation efficiency by supplying nutrients and promoting the growth of plants. This study aims to investigate the effects of AMF interactions and sewage sludge application on heavy metal phytoremediation in mine tailings. The samples of chrome tailings having very high heavy metal (Cr, Al, and Fe) contents were ameliorated by phytoremediation enhanced by inoculation of Glomus mosseae or Glomus intraradices and application of three different doses of sewage sludge and buffer soil. The results showed that AMF inoculation improved the efficiency of phytoremediation by increasing the metal uptake of plants. The sludge application improved the growth of plants. The combined Glomus mosseae and sludge (20 g/kg) amendments resulted with the highest plant heavy metal uptake and phytoremediation efficiency. This study offers confirmation on the role of the plant biomass and phytoextraction efficiency interactions in Cr mine tailings as well as mycorrhizal associations and the contribution of the sewage sludge to the plants growth. The outcome of the study confirms that Glomalin related protein rose with the mycorrhizal associations. Meanwhile, the sewage sludge also helped the plant to propagate glomalin protein.
Keywords: Phytoremediation.; Vesicular-arbuscular mycorrhizas.; Sewage sludge.; Tailings (Metallurgy) -- Environmental aspects.; Mineral industries -- Waste disposal -- Environmental aspects.